Rejection of the name Borreliella and all proposed species comb. nov. placed therein. Issue 5 (22nd April 2020) - Margos, Gabriele; Castillo-Ramirez, Santiago; Cutler, Sally; Dessau, Ram B.; Eikeland, Randi; Estrada-Peña, Agustin; Gofton, Alexander; Graña-Miraglia, Lucía; Hunfeld, Klaus-Peter; Krause, Andreas; Lienhard, Reto; Lindgren, Per-Eric; et al.
Abstract : Rejection ( nomen rejiciendum ) of the name Borreliella and all new combinations therein is being requested on grounds of risk to human health and patient safety (Principle 1, subprinciple 2 and Rule 56a) and violation to aim for stability of names, to avoid useless creation of names (Principle 1, subprinciple 1 and 3) and that names should not be changed without sufficient reason (Principle 9 of the International Code of Nomenclature of Prokaryotes).